If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -3 = -10 Reorder the terms: -3 + 9x = -10 Solving -3 + 9x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 9x = -10 + 3 Combine like terms: -3 + 3 = 0 0 + 9x = -10 + 3 9x = -10 + 3 Combine like terms: -10 + 3 = -7 9x = -7 Divide each side by '9'. x = -0.7777777778 Simplifying x = -0.7777777778
| 5x-5=-7 | | x+3=7x-15 | | 9=4(3k-4) | | 1.1x+3.2+0.2x-1.4=0 | | 39.34+2.56=56.03x | | 45x-33=87 | | 3(g-21)=2(10+g) | | 34x=32 | | 69=h+2h+(h-7) | | 66-34=x | | 10000+5.75x-25y= | | 8x+6(x-2)=-5(x-4)-x+8 | | (m-2)(m+2)=64 | | 5b-(4b+2)=14-2b+11 | | m^2-4m-62=-2 | | 10(-x+2)=-3(7x+2) | | (y-7)=2(x+2) | | 14x+(2-x)=6(2x-1) | | 7(x+5)+3=6(x+5) | | 4v-2=30 | | 40+6=n-3 | | Y-5=4(x+6) | | 2=10c-4(2-9) | | y=-2x^2+16x-34 | | y=-2x^2+16-34 | | 9(x+3)=4x-4 | | 18=9 | | 10y-2y=646 | | -26+x+2=16 | | .5x+5=7+1 | | X+2=4x-4-5x+2 | | 6x-14-4x=28 |